Genetic Variation on Upland Rice (Oryza sativa L.) Landraces of Nagalandâ€ - Gurung, G.; Seyie, K.; Sharma, M. B.; Kolom, R.; Ozukum, C. (Indian Journal of Hill Farming, 2018)
The success of most crop improvement programs largely depends upon the genetic variability and the heritability of desirable traits. The magnitude and type of genetic variability help the breeder to determine the selection criteria and breeding schemes to beused for improvement purposes. An experiment was conducted under NU: SASRD during kharif 2015 to estimate the genetic variability, heritability and correlation coefficient in ten genotypes of upland paddy evaluated in a randomized block design with three replications. Observations were recorded for ten quantitative traits. Genetic variability analysis revealed that, the genotypic coefficient of variation was highest for grain yield per plant followed by percent sterile spikelets, panicle weight, and ear bearing tillers. Heritability values for almost all the characters were found to be high. High heritability with high genetic advance was found for plant height. Percent sterile spikelets showed high heritability with moderate value of genetic advance. Grain yield per plant showed strong significant positive genotypic association with 100 seed weight, panicle weight, ear bearing tillers and panicle length.